Cover Crop Soil Legacies Alter Phytochemistry and Resistance to Fall Armyworm (Lepidoptera: Noctuidae) in Maize. Issue 4 (6th June 2021) - Davidson-Lowe, Elizabeth; Ray, Swayamjit; Murrell, Ebony; Kaye, Jason; Ali, Jared G
Abstract: Plant-soil feedbacks can mediate aboveground plant–herbivore interactions by impacting plant chemistry. Given that soil legacies and agricultural practices are closely tied, a better understanding of soil legacy cascades and their application in pest management are needed. We tested how cover crop legacies alter resistance to fall armyworm ( Spodoptera frugiperda Smith, Lepidoptera: Noctuidae) in maize ( Zea mays L., Poales: Poaceae). We compared herbivore performance and behavior of fall armyworm larvae on maize grown after four cover crop treatments: a leguminous mycorrhizal cover crop (pea: Pisum sativum L., Fabales: Fabaceae), a nonleguminous mycorrhizal cover crop (triticale: x Triticosecale Wittm. Ex A. Camus, Poales: Poaceae), a nonleguminous nonmycorrhizal cover crop (radish: Raphanus sativus L., Brassicales: Brassicaceae), and no cover crops (fallow). Soil inorganic N was highest in pea treatments and lowest in triticale treatments, while maize AMF colonization was greatest when grown after mycorrhizal cover crops compared to nonmycorrhizal or no cover crops. Cover crop legacies altered the emission of maize volatiles and fall armyworm larvae oriented toward odors emitted by maize grown after radish more frequently than triticale in olfactometer assays. Additionally, larvae performed better and consumed more leaf tissue when feeding on maize grown after radish and poorest on plants grown after triticale. When damaged by fall armyworm, maize grown after triticale expressed higher levels of lipoxygenase-3 (lox3), while plants grown after radish upregulated maize proteinase inhibitor (mpi) gene expression. Our results highlight the importance of appropriate cover crop selection and suggest that triticale could strengthen maize resistance to fall armyworm. Graphical Abstract: